2012
DOI: 10.5455/msm.2012.24.151-156
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae and Helicobacter Pylori Serology - Importance in Patients with Coronary Heart Disease

Abstract: Background:Chronic infections in CHD are due to one or both of the organisms Chlamydia pneumoniae and Helicobacter pylori.Aim:To examine the association between serum markers of Chlamydia pneumoniae and Helicobacter pylori infection and markers of myocardial damage. in patients with acute coronary syndrome (ACS), with chronic coronary artery disease (CAD) and in–control group.Material and methods:Sera were taken from a total of 153 subjects. Subjects were divided in three groups: 64 patients with ACS; 53 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…A multicenter, retrospective cohort study showed that Staphylococcus aureus bacteremia causes significant morbidity and mortality in patients with pre-existing immunosuppression, an aspect confirmed by our study as well [47]. Staphylococcus aureus is not typically associated with chronic coronary syndrome, which is a pathological process characterized by atherosclerotic plaque accumulation in the epicardial arteries; however, some studies have shown that there may be an association between this latter cardiac pathology and bacterial infections such as Chlamydia pneumoniae and Helicobacter pylori [48][49][50]. We found a strong correlation between chronic coronary syndrome and the presence of Staphylococcus aureus in the COVID-19-positive group.…”
Section: Discussionsupporting
confidence: 83%
“…A multicenter, retrospective cohort study showed that Staphylococcus aureus bacteremia causes significant morbidity and mortality in patients with pre-existing immunosuppression, an aspect confirmed by our study as well [47]. Staphylococcus aureus is not typically associated with chronic coronary syndrome, which is a pathological process characterized by atherosclerotic plaque accumulation in the epicardial arteries; however, some studies have shown that there may be an association between this latter cardiac pathology and bacterial infections such as Chlamydia pneumoniae and Helicobacter pylori [48][49][50]. We found a strong correlation between chronic coronary syndrome and the presence of Staphylococcus aureus in the COVID-19-positive group.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have already found the relationship between C. pneumoniae infection and coronary artery disease risk and prognosis (35,36). Our meta-analysis indicated that C. pneumoniae infection was significantly associated with an increased risk of cerebral infarction, and sensitivity analyses suggested the results were robust.…”
Section: Discussionmentioning
confidence: 99%
“…homocysteine, free radicals, cytokines, and chemokines) so that the outcome would be local and systemic intra-artery inflammation, which in turn results in atherosclerosis and thrombosis(22). Taking into account that the bacteria can prevent blood supply to walls of the heart, Helicobacter pylori infection may directly act as a pathogen on the wall of arteries and cause coronary diseases or indirectly cause inflammation(53, 54). If the relationship between Helicobacter pylori infection and cardiovascular diseases is proven, one may conclude that treating the infection reduces OR of the diseases and the pertinent events.…”
Section: Discussionmentioning
confidence: 99%